2022
DOI: 10.3389/fneur.2022.737667
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Poor and Favorable Outcome Prediction With Machine Learning After Mechanical Thrombectomy in Acute Ischemic Stroke

Abstract: Background and PurposeOutcome prediction after mechanical thrombectomy (MT) in patients with acute ischemic stroke (AIS) and large vessel occlusion (LVO) is commonly performed by focusing on favorable outcome (modified Rankin Scale, mRS 0–2) after 3 months but poor outcome representing severe disability and mortality (mRS 5 and 6) might be of equal importance for clinical decision-making.MethodsWe retrospectively analyzed patients with AIS and LVO undergoing MT from 2009 to 2018. Prognostic variables were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Similarly, Mutke et al. were able to predict favorable functional outcome (mRS 0‐2) in AIS patients with anterior circulation LVOs who were treated with mechanical thrombectomy with an AUROC of 0.73, once again utilizing the predictors such as age and NIHSS score 38 . Other studies that used conventional predictors to predict the favorable functional outcome (mRS 0‐2) in AIS patients with LVOs had AUROCs of 0.856, 0.86, 0.91, 0.90, and 0.82 18,19,39–41 .…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Mutke et al. were able to predict favorable functional outcome (mRS 0‐2) in AIS patients with anterior circulation LVOs who were treated with mechanical thrombectomy with an AUROC of 0.73, once again utilizing the predictors such as age and NIHSS score 38 . Other studies that used conventional predictors to predict the favorable functional outcome (mRS 0‐2) in AIS patients with LVOs had AUROCs of 0.856, 0.86, 0.91, 0.90, and 0.82 18,19,39–41 .…”
Section: Discussionmentioning
confidence: 92%
“…This model may significantly help doctors diagnose the hemorrhage transformation of patients with acute ischemic stroke. In 2022, Mutke et al [ 49 ] collected MR images and clinical data of 210 patients with acute ischemic stroke and large vessel occlusion for whom mechanical thrombectomy was performed. The data were used to predict favorable and poor outcomes after mechanical thrombectomy.…”
Section: Machine Learning Algorithms Trained On Image Datamentioning
confidence: 99%
“…In addition, although previous studies have suggested that conventional LR can provide a clinical prediction model that is easy to interpret, when conventional LR is used for complex multivariate non-linear relationships, complex transformations are often required owing to low robustness and multicollinearity between variables ( 14 ). Therefore, recent work has highlighted the potential of machine learning (ML) algorithms for stroke-related complications in stroke patients ( 15 , 16 ). Savarraj et al suggested that ML models significantly outperform conventional LR in predicting functional outcomes and has the potential to improve SAH management ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Savarraj et al suggested that ML models significantly outperform conventional LR in predicting functional outcomes and has the potential to improve SAH management ( 17 ). The ML models possess the potential to outperform conventional linear or logistic regression models due to their exceptional ability in identifying intricate and nonlinear relationships among a multitude of prognostic variables ( 16 ). Thus, in this study, we conducted five ML prediction model, which contains support vector machine (SVM), logistic regression (LR), random forest (RF), multilayer perceptron (MLP), K-nearest neighbor (KNN) and extreme gradient boosting (XGBoost) for the prediction of POP within 30 days in aSAH patients after surgical treatment.…”
Section: Introductionmentioning
confidence: 99%